Study on Runoff Simulation in Xinglong Area Jinan Based on Low Impact Development. Issue 5 (February 2019) - Wang, Yanru; Hou, Yunhan; Xu, Zhenghe
Abstract: This paper uses SWMM software to build stormwater model in different land use scenarios (natural model, traditional urban development mode, low impact development mode), and simulates runoff processes of different return periods (2-year return period, 10-year return period, 20-year return period). Comparing and analyzable the runoff effect under different land use situations according to the simulation results, the result shows that the comparison from excellent to poor is followed by low impact development mode, natural mode and traditional urban development mode, it fully proved the role of low-impact development model in absorbing runoff and reducing flood peak.